Acylation of anisole with long-chain carboxylic acids over wide pore zeolites - Wagholikar, S. G.; Niphadkar, P. S.; Mayadevi, S.; Sivasanker, S. (Applied Catalysis A-General, 2007)
The acylation of anisole with long-chain carboxylic acids (hexanoic, octanoic and decanoic) has been studied over three large pore zeolites-beta (BEA), faujasite (FAU) and mordenite (MOR). The acylation of anisole with the long chain acids produced mainly the ketone (4-methoxy phenyl alkyl ketone) and small amounts of the ester (phenyl alkanoate). The results revealed the reaction to be influenced by the type of zeolite and its Si/Al ratio (acidity) besides the chain length (carbon number) of the carboxylic acid. In the acylation of anisole with hexanoic acid, the activity of the zeolites increased with dealumination as it led to the generation of mesopores that resulted in a decrease in diffusion resistance of the zeolites. The reactivity of the acids in the acylation reaction was found to decrease with increase in the carbon number. The experimental data have been fitted into a pseudo first order kinetic model. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Acylation; Anisole; decanoic acid; hexanoic acid; octanoic acid; zeolites

Analysis of a membrane reactor: influence of membrane characteristics and operating conditions - Tanna, Nikunj P.; Mayadevi, S. (International Journal of Chemical Reactor Engineering, 2007)
Modeling of an esterification reaction in a batch pervaporation membrane reactor (PVMR), and an analysis of the PVMR performance under different reaction conditions for different membrane characteristics are presented. Esterification of ethyl alcohol with acetic acid was considered as the model reaction. The PVMR performance for this reaction could be represented by a 2-step series model. The PVMR performance was similar to that of the batch reactor when both the reactors were in the kinetic regime. However, the performance of the PVMR was superior to that of the batch reactor when both were in the intermediate/equilibrium regime of the reaction. In these regions, the PVMR performance was influenced/limited by the membrane flux and selectivity. The analysis showed that the membrane flux affected the PVMR performance in the intermediate region and the membrane selectivity affected the performance in the equilibrium regime. Further, the limitations introduced by a low-flux membrane could be overcome by appropriate selection of the membrane area and that due to poor selectivity could be compensated to a certain extent by adjusting the feed ratio.
Keywords: comparison; Esterification; membrane reactor; performance; pervaporation membrane

Adsorption of fluoride ions by Zn-Al layered double hydroxides - Mandal, Sujata; Mayadevi, S. (Applied Clay Science, 2008)
Zn-Al layered double hydroxides (LDHs) with different molar ratios Zn/Al (0, 0.17, 0.34, 0.97, 3.47, proportional to) were prepared by the co-precipitation of chlorides, characterized and evaluated for their fluoride adsorption at room temperature from aqueous solutions. The fluoride adsorption of the as-synthesized LDHs was influenced by the chemical composition of the LDHs and ZA-11 (Zn/Al = 0.97) had the highest capacity for fluoride adsorption (1.14-4.16 mg/g). The adsorption increased after calcination of the LDH up to 500 degrees C. The equilibrium data were fitted to the Freundlich, Langmuir, and Temkin equations. The kinetics of fluoride adsorption followed the pseudo-second order model. (C) 2007 Elsevier B.V All rights reserved.
Keywords: Adsorption; Anionic clay; Fluoride; Layered double hydroxide

Adsorption of aqueous selenite [Se(IV)] species on synthetic layered double hydroxide materials - Mandal, Sujata; Mayadevi, S.; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2009)
{Layered double hydroxide materials (Zn/Al, Mg/Al, Zn/Fe) with varying composition (M(2+):M(3+) molar ratio

Adsorption of cresols on zinc-aluminium hydroxides - a comparison with zeolite-X - Vijayakumar, J.; Chikkala, Suresh K.; Mandal, Sujata; Mayadevi, S. (Separation Science and Technology, 2011)
Liquid phase adsorption of m-cresol on Zn-Al hydroxide adsorbents with three different Zn/Al molar ratios was studied in different solvents and compared with commercial zeolite 13X. Among the three adsorbents, ZA-16 showed adsorption capacity similar to commercial zeolite 13X. Solvents used for the preparation of m-cresol solution were found to influence the adsorption capacity. The adsorption capacity was maximum for the solution of m-cresol in n-hexane. Conventional Langmuir and Freundlich adsorption isotherm equations were used to explain the adsorption behavior. The kinetics of m-cresol adsorption followed the first-order Lagergren kinetic model. p-Cresol/m-cresol separation factor was the highest when toluene was used as the organic medium.
Keywords: Adsorption; cresol; zeolite; zinc-aluminium hydroxide

Alkylation of anisole with 1-hexene and 1-hexanol over zeolite H-beta - Surse, P. V.; Wagholikar, S.; Mayadevi, S.; Sivasanker, S. (Reaction Kinetics Mechanisms and Catalysis, 2011)
An examination of the kinetics of the alkylation of anisole with 1-hexene and 1-hexanol to produce alkylates over zeolite H-beta is presented. Anisole alkylation is found to occur by a set of parallel reactions when hexene is used as the alkylating agent. When hexyl alcohol is the alkylating agent, the reaction follows a multi-step parallel-series mechanism to form monoalkylates and dihexylether. With 1-hexene, a group of isomeric alkylates, viz., ortho-2-hexyl anisole (2-OHA), ortho-3-hexyl anisole (3-OHA), para-2-hexyl anisole (2-PHA), and para-3-hexyl anisole (3-PHA) was obtained. With hexanol, the olefin (hexene) and dihexyl ether were obtained additionally. The influence of process parameters like temperature, catalyst quantity, and alkylating agent on reaction behavior is reported.
Keywords: Alkylation; Anisole; H-beta; Hexene; Hexyl alcohol

Alginate and hydrotalcite-like anionic clay composite systems: synthesis, characterization and application studies - Mandal, Sujata; Patil, Varsha S.; Mayadevi, S. (Microporous and Mesoporous Materials, 2012)
Hydrotalcite-like anionic clays (Zn/Al and Mg/Al) were intercalated with sodium alginate to form organic-inorganic composite adsorbents for water treatment applications. The synthesized composites were characterized using different characterization techniques viz. XRD, DRIFTS, SEM and surface area/porosity analysis. The adsorption potential of the alginate-clay composites was examined for removal of fluoride ions and Orange II dye from water by adsorption. Our studies revealed that these composites had high adsorption capacity for the adsorption of fluoride and Orange II dye from aqueous solutions. The adsorption capacity of the composites was considerably higher than that of either alginate or clay, used individually. The results indicated that these materials might be useful sorbents for groundwater purification/effluent treatment. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Alginate; Anionic clay; Composite; Fluoride; Orange II dye